Development of Hypermedia-Based Interactive Learning Tools to Improve Student Social Science Learning Outcomes - Rochmattulloh, Ardi Samudra; Prastowo, Srihandono Budi; Farisi, Mohammad Imam (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This study aims to produce hypermedia-based learning tools that are valid, practical and effective to improve the social science learning outcomes of elementary school students. This research used the Research and Development method with the ADDIE model using an experimental design. The population of this study was teachers of SDN Tamanbaru and SDN Kebalenan along with grade IV students of SDN Tamanbaru amounting to 13 students and grade IV of SDN Kebalenan amounting to 97 students. This research instrument used observation, tests, and questionnaires. Meanwhile, the data analysis techniques were validity test, reliability test, N-Gain test, and Independent t-test. The results showed: 1) hypermedia-based learning devices have very valid quality with a score of 92.5% and an average reliability of 90.2%; 2) Effective category hypermedia-based learning tools based on the N-Gain value on the limited test of 31.76%; and the experimental class at 34.2%; the results of the independent t-test test obtained the value of the sig lavene's test was 0.203>0.05 and the equality of means obtained a sig of 0.034<0.05; 3) Hypermedia-based learning tools are very practical based on student responses to limited tests, with an average score of 87.70% and the average score of experimental classes of 91.07%; and the ability to manage the learning process on limited tests by 91.2% and experimental classes by 96.4%. Thus, hypermedia-based learning tools are valid, practical, and effective so that they can be used in the social science learning process on the theme of the diversity of work in grade IV elementary school.